Deformable object simulation with fluid model - Zhong, Yongmin; Shirinzadeh, B.; Smith, J. (Curran Associates, 2006)
Virtual reality based surgery simulation is expected to provide benefits in many aspects of surgical procedure training and evaluation. To this end, significant research effort has been dedicated to simulating the behaviors of deformable objects. These researches can be divided into two types. One class of studies is focused on real-time simulation such as mass-spring models [Zhang et al 2004, Choi et al2003] and spline surfaces used in deformation [Terzopoulos et al 1987, Rotnes etal 2001]. The advantage of this method is that the computation is less time consuming and the algorithm is easier to be implemented. However, the method does not allow accurate modelling of material properties, and more importantly, increasing the number of springs leads to a stiffer system. The other class of investigations is devoted to accurate deformation modelling such as Finite Element Method (FEM) [Cotin et al 1999, Basdogan et al 2001] and Boundary Element Method (BEM) [James and Pai 1999, Monserrat et al 2001]. In FEM or BEM, rigorous mathematical analysis based on continuum mechanics is applied to accurately model the mechanical behaviors of soft objects. However, these methods are computationally expensive and only the simplest variant such as linear shape functions has been used in deformable object simulation. The pre-calculation [Cotinet al 1999], matrix condensation [Bro-Nielsen et al 1998] and the space and time adaptive level-of-detail [Debunne et al 2001] techniques are used to enhance the computational performance.